(untitled) (Bangladesh Agronomy Journal, 2022)
The production area of chickpea in Bangladesh is decreasing day by day due to the competition with higher yielding crop which is/or profitable than chickpea. As such, the experiment was undertaken at Regional Agricultural Research Station, Jashore during 2019-2020 and 2020-2021 to study the effect of most suitable method of de-topping (nipping) in chickpea (var. BARI Chola-10) for its growth and yield improvement. Treatments were imposed in a split-plot design where in main plot : time of nipping : 30 days after emergence (DAE) , 40 DAE E3- 50 DAE and in sub-plot: different heights of nipping practices: Control, Nipping 5 cm from growing tip, Nipping 8 cm from growing tip and Nipping 10 cm from growing tip. In interaction treatment, the highest days to flower (68), days to mature (112), vegetable yield (703 kg ha-1) was observed when chickpea plants were de-topped after 50 DAE at 10 cm from growing tip. The highest plant height (46 cm) was observed when de-topping at 40 DAE was done at 10 cm from growing tip. Seed yield (1419.95 kg ha-1) and Marginal Benefit Cost Ratio (MBCR) (13.1) was recorded maximum when chickpea plants de-topped 50 DAE at 5 cm from growing tip. De-topping practices in chickpea (var. BARI Chola-10) after 50 DAE at 5 cm from growing tip could maximize the productivity of chickpea. Bangladesh Agron. J. 2021, 24(2): 109-113